Description of sinodiplectanotrema malayanum n. sp (Monogenea: Diplectanidae), with comments on the taxonomic position of the genus - Lim, L.H.S.; Tan, W.B.; Gibson, D.I. (Kluwer (now part of Springer), 2010)
Monogeneans identified as Sinodiplectanotrema malayanum n. sp. were collected from the fish Pennahia anea (Sciaenidae) off the west coast of Peninsular Malaysia. The new species is recognised on the basis of morphometrical differences in the anchors, marginal hooks and eggs and apparent differences in the 28S rDNA sequence data. The new species possesses features (ovary looping the intestinal caecum, body spines, a vagina and haptoral reservoirs) not noted in the original description of the type and only other species of the genus, S. argyrosomus Zhang, 2001, necessitating the re-assignment of the genus to the Diplectanidae Monticelli, 1903, a move which is supported by 28S rDNA evidence. Sinodiplectanotrema is redefined on the basis of the observation of several features not included in the original diagnosis.